Stratégies de salariés face à l’introduction de nouvelles méthodes de management - Michel Feynie (La Nouvelle Revue du Travail)
The text builds on an anthropological survey conducted within a state-owned enterprise to show how the introduction of new management methods restricts employees' autonomy and imprisons them within models. It then discusses models' excessive and sometimes ridiculous aspects. Based on these observations, it describes the different strategies that employees use to mitigate, get around or escape such directive methods.